2000
DOI: 10.1051/analusis:2000122
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic extraction of some divalent metal cations with 3-phenyl-4-benzoylisoxazol-5-one and P=O donor ligands in chloroform

Abstract: Abstract. The synergistic extraction of some divalent cations (Cd, Cu, Mn and Zn) in chloroform, with 3-phenyl-4-benzoylisoxazol-5-one (HPBI) in the presence of various synergistic agents: trioctylphosphine oxide (TOPO), octyl(phenyl)(N,N-diisobutylcarbamoylmethyl)phosphine oxide (CMPO) and bis(diphenylphosphinyl)methane (BDPPM) has been studied. It is compared with the extraction in toluene. Due to various factors (e.g. extractant-diluent or extractant-synergist interactions), the stoichiometry of the extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…35 It is well known that the acidity of the extractant is one of the predominant factors governing extractability, i.e., the lower the pK a value, the larger is log K exc . Torkestani et al, 36 Sekine et al, 37 and Reddy and coworkers 22 stated that the interaction between the chelating agent and a neutral oxo-donor in CHCl 3 are, in general, weaker when the diluent itself has strong interaction with the oxo-donor. However, the difference in the polarity of the diluents is higher (dielectric constant of chloroform = 4.9, 1,2-dichloroethane = 10.4).…”
mentioning
confidence: 99%
“…35 It is well known that the acidity of the extractant is one of the predominant factors governing extractability, i.e., the lower the pK a value, the larger is log K exc . Torkestani et al, 36 Sekine et al, 37 and Reddy and coworkers 22 stated that the interaction between the chelating agent and a neutral oxo-donor in CHCl 3 are, in general, weaker when the diluent itself has strong interaction with the oxo-donor. However, the difference in the polarity of the diluents is higher (dielectric constant of chloroform = 4.9, 1,2-dichloroethane = 10.4).…”
mentioning
confidence: 99%
“…[23,24,35,36] The results may be explained based on the acid dissociation constant (pKa) value of the chelating ligand shown in Table VI. The orientation tendency of the nonbonding electron pair of the chelating ligand toward the metal ion depends on its pKa value.…”
Section: G Degree Of Synergism and Equilibrium Constant In Extractionmentioning
confidence: 99%
“…J.-P. Brunette et al [22,24] reported the synergistic extraction of copper with 3-phenyl-4-benzoyl isoxazol-5-ones (HPBI) in the presence of tri-n-octylphosphine oxide (TOPO) in toluene and chloroform. They have indicated that copper is extracted in the form of Cu(PBI) 2 .TOPO complex, without containing any water molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Many advantages, such as the enhancement of separation ability and the appearance of new function as well as the improvement of extractability, are expected by the introduction of synergic extraction systems. Previously, a number of synergic liquid-liquid extraction studies of the divalent metal ions have been carried out using various synergists, like tri-n-octyl phosphine oxide (TOPO), tributyl phosphate (TBP), and 1,10-phenanthroline (PHEN); acidic organophosphorus, and acyl-pyrazolone or -isoxazolones b-diketones as extractants [7][8][9][10][11][12][13][14][15][16] . The Schiff bases were found to be powerful extractants for metal ions in recent years [17][18][19][20][21][22][23][24][25][26][27] .…”
Section: Introductionmentioning
confidence: 99%